Perencanaan Pengelolaan Dana Zakat Dan Potensi Zakat Provinsi Bangka Belitung - Iswanto, Rosi; Azis, Ismi Yati (LENTERNAL: Learning and Teaching Journal, 2023)
The purpose of this research is to find out the planning of the Zakat Fund Management of Bangka Belitung Province. for the successful assembly of the Basnas of Bangka Belitung Province. This article uses descriptive methods supported by secondary data obtained from various sources. Zakat comes from the word zaka, which means good, blessing, growing, clean, and increasing. Allah requires that those who are eligible to receive the Zakat, as it is known, receive it. (muzakki). This article is a descriptive article because it describes how to plan fund management and potential fund management in Basnas Province, Bangka Belitung. The accumulation of Zakat in 2015 amounted to Rs. 1,207,413,434, in 2016 it increased to Rs. 1,726,183,874, and in the following year, in 2017, the re-accumulation experienced a very significant increase of Rs. 6,156,081,724. The increase came after Baznas Bangka Belitung made various attempts, including by taking a bureaucratic approach to the provincial government through the governor's policy to instruct the Muslim ASN surrounding the government of the Bangka Islands on the obligation of zakat.